Functional morphometry of the pterygoid hamulus. A comparative study of modern and medieval populations - Komarnitki, Iulian; Mankowska-Pliszka, Hanna; Ungier, Ewa; Dziedzic, Dawid; Grzegorczyk, Michal; Tomczyk, Agnieszka; Ciszek, Bogdan (Anthropological Review, 2019)
The pterygoid hamulus (PH) is located in the infratemporal fossa and is part of the pterygoid process of the sphenoid bone. Its location on the cranial base and the multitude of anatomical structures whose attachments lie on the surface of the pterygoid hamulus make it of high functional and topographic significance. Due to insufficient literature on the PH morphometry, we decided to study this issue using modern and archaeological material. In total, 99 observations were subjected to quantitative and qualitative analysis (50 - from modern times and 49 - from medieval times). On the basis of the statistical analysis, statistically significant differences in the length of PH were found with respect to age and sex. Statistically significant differences in the PH width were also noticed with respect to sex and the period of origin. The results obtained may help better understand the development mechanism of the pterygoid hamulus bursitis.